Prototype of single degree of freedom optical resolver - Islam, Saiful; Saleh, Tanveer; Latief, Marsad; Mohd Razib, Mohd Asyraf; Abdul Muthalif, Asan Gani (IOP Publishing Ltd, 2019)
Optical resolvers are helpful for a wide variety of application, for example, automation and manufacturing industries. Different kinds of optical resolvers are available based on different material properties. In this paper, a prototype of a single Degree of Freedom optical resolver for measuring the angle of rotation is proposed. The device is based on the combination of the single wavelength (partially polarized) laser beam, a linear polarizer and a photodetector circuit is used for the rotational angle measurement. We present the result of sensitivity, accuracy and repeatability test to ensure the proper execution of single DOF optical resolver. The sensitivity of a single DOF optical resolver is around 0.467 V/degree and the standard deviation is 0.2 Volt. We obtained highly accurate and repeatable measurements according to the variation of the angle of the polarizer. Newly developed prototype optical resolver is cost effective, compact in size, no electromagnetic interference.